Telegram Based Smart Sink with Voice Guide - Donny Wiraputra; Izza Anshory; Akhmad Ahfas; Arief Wisaksono (Procedia of Engineering and Life Science, 2021)
Hands are the main medium of carrying germs, bacteria, and viruses when doing activities, so hand washing is a necessity to prevent the spread of various diseases. The purpose of this research is to innovate the sink to make it more interesting because this tool can remind people in front of it. It is also the application of health protocols in the global pandemic. This tool is equipped with an HC-SR04 sensor to detect humans, then the speaker sounds an invitation to diligently wash your hands. This tool can work automatically when the Proximity sensor near the faucet detects the hand, it activates the soapy water pump for 3 seconds, then pauses 15 seconds, and then releases clean water for 10 seconds, then the speaker reads the handwashing guide. To prevent running out of water and soap, the HC-SR04 sensor is equipped to detect the capacity of tendons connected to notifications via telegram. The result is HC-SR04 accuracy in detecting people by 99.4%, reading the water level of 98.3% and soapy water 98.2%, notifications using Telegram successfully sent within 220-250 seconds for 5 experiments, the best Simcard used is Telkomsel with an average time of 21.6 seconds.